Cultura geral e práticas educativas para o ensino industrial no Boletim da CBAI (1947-1961) - Campos, Ísis de Freitas (2022)
This dissertation aims to understand which ideas circulated in the Boletim da CBAI (1947- 1961), a periodical published by the Brazilian-American Commission for Industrial Education (CBAI – Comissão Brasileiro-Americana de Educação Industrial), in relation to the subjects of General Culture and Educational Practices, that appears in the curriculum of industrial education. The CBAI, officially maintained from 1946 to 1962, operated from the articulation between Brazil and the United States for the development of industrial education, organizing this branch of education based on what was established in the Organic Law of Industrial Education, of 1942, until the National Education Guidelines and Framework Law of 1961. That legislation was responsible for the structuring of a curriculum that set out the subjects of General Culture and Educational Practices, with components that also appeared in secondary education, and those of Technical Culture, more directed for the professions to be learned. Based on Apple (2008), it is questioned how the proposals for teaching General Culture and Educational Practices would also be adequate to the logic of training for productivity in the industry, understanding that the curriculum is designed from the demands of social relations and productive, which, in this case, are connected to the industrialization project. From Catani (1996), we understand the potential of educational journals for the study of discourses about ideal ways of carrying out educational work. In this sense, the CBAI Bulletin was used as the main source of research, being analyzed based on the methodological assumptions of History Through the Press (ZICMAN, 1985) and content analysis (ARÓSTEGUI, 2006; MORAES, 1999). For this, it was first necessary to build a biography of the concepts (CASTANHA, 2011) of General Culture and Educational Practices, in order to identify changes in the legislation of the period. Also, as secondary sources, newspapers from the Hemeroteca Digital Brasileira and documents taken from the Gustavo Capanema archive at the Center for Research and Documentation of Contemporary History of Brazil (CPDOC) were used to assist in the interpretation process. As a result of the study, it was identified that the CBAI Bulletin was an area to defend the teaching of General Culture and Educational Practices. However, this teaching should be connected to technical knowledge, an appropriation of the New School perspective of combining theory with practice. For the application of this proposal, problems were detected such as the lack of specific teacher training and bibliography, for example.